Surgical treatment for severe pediatric tracheobronchomalacia: the 20-year experience of a single center - Caroline Gargioni Barreto; Marcelo Costamilan Rombaldi; Felipe Colombo de Holanda; Iara Siqueira Lucena; Paola Maria Santis Isolan; Russell Jennings; José Carlos Fraga (Elsevier, 2024)
Objective: In children with tracheobronchomalacia, surgical management should be reserved for the most severe cases and be specific to the type and location of tracheobronchomalacia. The goal of this study is to describe the presentation and outcomes of children with severe tracheobronchomalacia undergoing surgery. Methods: Retrospective case series of 20 children operated for severe tracheobronchomalacia at a tertiary hospital from 2003 to 2023. Data were collected on symptoms age at diagnosis, associated comorbidities, previous surgery, age at surgery, operative approach, time of follow-up, and outcome. Surgical success was defined as symptom improvement. Results: The most frequent symptoms of severe tracheobronchomalacia were stridor (50 %), cyanosis (50 %), and recurrent respiratory infections (45 %). All patients had one or more underlying conditions, most commonly esophageal atresia (40 %) and prematurity (35 %). Bronchoscopy were performed in all patients. Based on etiology, patients underwent the following procedures: anterior aortopexy (n = 15/75 %), posterior tracheopexy (n = 4/20 %), and/or posterior descending aortopexy (n = 4/20 %). Three patients underwent anterior aortopexy and posterior tracheopexy procedures. After a median follow-up of 12 months, 16 patients (80 %) had improvement in respiratory symptoms. Decannulation was achieved in three (37.5 %) out of eight patients with previous tracheotomy. The presence of dying spells at diagnosis was associated with surgical failure. Conclusions: Isolated or combined surgical procedures improved respiratory symptoms in 80 % of children with severe tracheobronchomalacia. The choice of procedure should be individualized and guided by etiology: anterior aortopexy for anterior compression, posterior tracheopexy for membranous intrusion, and posterior descending aortopexy for left bronchus obstruction.